Jurnal/Artickle/PKM PEMBERDAYAAN PELAKU UMKM DALAM PENGGUNAAN APLIKASI MARKET PLACE SEBAGAI MEDIA PEMASARAN ONLINE: PENGGUNAAN APLIKASI MARKET PLACE SEBAGAI MEDIA PEMASARAN ONLINE - Iriani, Nisma; Putera, Wahyudi; Mardia, Mardia; Rahman, Abd; Arjang, Arjang; Rostini, Rostini; Samuddin, Syurwana Farwita; Syahribulan, Syahribulan (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is a strategic step in facing the challenges of economic digitalization. This study aims to explore the impact of using marketplace applications as an online marketing medium on the sustainability and growth of MSME businesses. Digital marketplaces allow MSMEs to access wider markets, reduce operational costs, and increase marketing efficiency. However, challenges such as limited digital literacy, lack of trust in online transactions, and adaptation to technology are significant obstacles. The research approach used a survey method and in-depth interviews with 100 MSME actors in various economic sectors. The results showed that 75% of respondents experienced an increase in sales after using the marketplace, while 60% acknowledged an increase in digital competence through training related to the platform. The study also identified the importance of the role of government and private institutions in providing digital education, access to funding, and technology infrastructure for MSMEs. The conclusion of the study confirms that the use of marketplace applications is not only a modern marketing solution, but also encourages local economic empowerment. Recommendations are given to improve the effectiveness of training, collaboration between industry players, and technology integration to support MSME competitiveness in the digital era.